The Medical Importance of Snails " A review" - N. Ghulam, Israa (Pure Sciences International Journal of Kerbala, 2024)
This research article provides a comprehensive review of the medical importance of snails from a medical standpoint, whether negative or positive on humans and animals, and whether their effect is direct or indirect. The medical importance of snails in general is in two ways: either as a carrier of disease or as a source of therapeutic agents. There are many aquatic snails that are considered intermediate hosts for parasitic flatworms. Some of them contribute to the spread of schistosomiasis, for example, and it causes great concern for public health. This disease may lead to chronic disease and can lead to severe damage to some organs of the body. Some marine snails, such as cone snails, produce conotoxins. This toxin is a biologically active compound with pharmaceutical potential. It is a powerful neurotoxin that is being studied for its analgesic properties and the possibility of using it as new painkillers. The study of snail biology and their interactions with parasites and bioactive substances offers promising approaches to combating diseases and developing new medical treatments. This study was supported by pictures and diagrams of the life cycle of some snails to clarify some concepts.